Hyperbaric oxygen therapy for the treatment of radiation-induced macular ischemia - Shamim A Haji (Dove Medical Press, 2010)
Shamim A Haji1,2, Ronald EP Frenkel1,2,31Eye Research Foundation, Stuart, FL, USA; 2East Florida Eye Institute, Stuart, FL, USA; 3Bascom Palmer Eye Institute, Miami, FL, USAPurpose: To report a case of radiation-induced macular ischemia where vision and macular perfusion improved after hyperbaric oxygen (HBO) therapy.Methods: A 62-year-old male patient developed radiation-induced macular ischemia after he was treated with radiation for brain glioma. The patient presented with best spectacle-corrected visual acuity (BSCVA) acuity of 20/400 in his right eye. Optical coherence tomography (OCT) showed central macular thickness of 468 μm. The patient received focal laser, intravitreal triamcinolone, and HBO therapy.Results: The patient’s vision improved from 20/400 to 20/100 after focal laser and intravitreal triamcinolone. His central macular thickness improved from 468 μm to 132 μm. After receiving HBO therapy, his VA improved to 20/50 and fluorescein angiography showed improvement in macular perfusion.Conclusion: HBO therapy improves macular perfusion in patients with radiation-induced macular ischemia.Keywords: macular ischemia, visual acuity, hyperbaric oxygen therapy, macular perfusion